Increasing anthracyclines efficacy in Triple Negative Breast Cancer cells by disrupting cells defense mechanism and evaluating Caspase-3 as indicator for anthracyclines hematologic toxicity in breast cancer patients - Luo, Man (Nanyang Technological University, 2020)
Chemotherapy is the backbone of systemic treatment for triple negative breast cancer (TNBC), among which anthracyclines are important agents and represent the current standard treatment option. However, treatment failure usually happens due to the drug resistance developed by TNBC cells. Especially when metastasis occurs, the first line anthracycline drug for TNBC treatment, doxorubicin (DOX), usually loses its efficacy. The mechanism underlying the metastasis-acquired DOX resistance of TNBC cells remains to be elucidated. In the first part of this thesis, two-dimensional difference gel electrophoresis (2D-DIGE) proteomics was applied to compare the protein profiles between an apoptosis sensor-labeled TNBC cell line MDA-MB-231-C3 (231-C3) and its lung metastatic cell line 231-M1. The first part of this thesis demonstrates G6PD mediates metastasis-acquired as well as intrinsic DOX resistance of TNBC cells and shows G6PD is a potential therapeutic target for sensitizing TNBC towards DOX treatment. Another challenge associated with anthracyclines administration for breast cancer treatment is the dose-limiting hematologic toxicity, which often leads to treatment delay or even discontinuation and hence the treatment failure. The second part of this thesis is to establish the caspase-3 activation as an early indicator for hematologic toxicity in cancer patients receiving chemotherapy. Thirty-nine female non-metastatic breast cancer patients were recruited in this project. Through this clinical study, plasma caspase-3 level in cancer patients during chemotherapy course was proved to be a potential indicator of hematologic toxicity induced by anti-cancer drugs.